ANALISIS PENGELOLAAN PESERTA DIDIK UNTUK MENGEMBANGKAN KUALITAS PEMBELAJARAN DI SD ISLAM AN-NUR - Syachruroji, A.; Rokhmanah, Siti; Maulana, Ipan (Journal of Professional Elementary Education, 2024)
Management means organizing, carrying, or directing. Management carried out in schools is certainly closely related to the management of students. Student management is an effort to provide services that are provided as well as possible to students from the beginning of entering school to graduation to help the growth and development of students. This research was conducted with the aim of knowing how the management of students in SD Islam An-Nur. In conducting research, researchers use a qualitative approach with descriptive methods. The results showed that the management of participants at SD Islam An-Nur had been carried out very well and planned. This can be seen through the management process starting from planning, acceptance, placement, coaching, to evaluation that has been carried out in a structured manner. In its management, the school has prioritized the needs of students and involved all elements in the school to the parents of students to take part so that student management in the school can be carried out properly and optimally